2011
DOI: 10.1101/lm.1986911
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibition modulates hippocampus-dependent long-term memory for object location in a CBP-dependent manner

Abstract: Transcription of genes required for long-term memory not only involves transcription factors, but also enzymatic protein complexes that modify chromatin structure. Chromatin-modifying enzymes, such as the histone acetyltransferase (HAT) CREB (cyclic-AMP response element binding) binding protein (CBP), are pivotal for the transcriptional regulation required for long-term memory. Several studies have shown that CBP and histone acetylation are necessary for hippocampusdependent long-term memory and hippocampal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
181
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(202 citation statements)
references
References 38 publications
18
181
0
3
Order By: Relevance
“…Previously our laboratory has shown that HDAC inhibition is able to enhance long-term memory and synaptic plasticity (Vecsey et al, 2007) and rescue long-term memory deficits in CBP mutant mice when the mice are tested on object recognition (Stefanko et al, 2009), but not when they are tested on object-location recognition (Haettig et al, 2011). We therefore examined the ability of the HDAC inhibitor sodium butyrate (NaBut) to ameliorate memory impairments in Cbp flox/flox mice.…”
Section: Long-term Memory Is Not Rescued By Systemic Administration Omentioning
confidence: 99%
See 1 more Smart Citation
“…Previously our laboratory has shown that HDAC inhibition is able to enhance long-term memory and synaptic plasticity (Vecsey et al, 2007) and rescue long-term memory deficits in CBP mutant mice when the mice are tested on object recognition (Stefanko et al, 2009), but not when they are tested on object-location recognition (Haettig et al, 2011). We therefore examined the ability of the HDAC inhibitor sodium butyrate (NaBut) to ameliorate memory impairments in Cbp flox/flox mice.…”
Section: Long-term Memory Is Not Rescued By Systemic Administration Omentioning
confidence: 99%
“…They were trained 2 weeks later, and tested at 24 h following training. During training, mice were placed in an arena with two identical objects for a 10-min training session, which we have previously shown to result in long-term memory (Stefanko et al, 2009;Roozendaal et al, 2010;Haettig et al, 2011), and then tested at 24 h later in the same arena with one familiar object moved to a novel location (OLM; Figure 6a). AAV2/ 1-Cre infused Cbp flox/flox mice exhibited no significant long-term memory for the object location as compared with Cbp + / + mice (po0.05; Figure 6b).…”
Section: Long-term Memory For Object Location But Not Memory For Thementioning
confidence: 99%
“…Most previous studies examined the hippocampus-dependent contextual fear-conditioning task (Alarcon et al 2004;Levenson et al 2004;Vecsey et al 2007;Guan et al 2009;Peleg et al 2010) or extinction of fear memory Bredy and Barad 2008). Recently, memory enhancement by HDAC inhibitor treatment was observed for object-recognition memory (Stefanko et al 2009) and object-location memory (Haettig et al 2011). In contrast to object-location memory (Haettig et al 2011) and contextual fear conditioning (Vecsey et al 2007), the effect of HDAC inhibition on object-recognition memory does not require the CREB-CBP interaction (Stefanko et al 2009).…”
mentioning
confidence: 99%
“…Recently, memory enhancement by HDAC inhibitor treatment was observed for object-recognition memory (Stefanko et al 2009) and object-location memory (Haettig et al 2011). In contrast to object-location memory (Haettig et al 2011) and contextual fear conditioning (Vecsey et al 2007), the effect of HDAC inhibition on object-recognition memory does not require the CREB-CBP interaction (Stefanko et al 2009). This mechanistic distinction is supported by an anatomical dissociation in the effect of HDAC inhibitors on different forms of object-based memory (Roozendaal et al 2010).…”
mentioning
confidence: 99%
“…We can hypothesize that successful performance on the overlapping condition involves the integration of multiple or all events in the prefrontal cortex, thereby creating a stable representation of the overlapping object location in space. While the classic version of our stable condition, namely 24h-objectdisplacement memory, is usually described as a hippocampal-dependent task (Mumby, Gaskin et al 2002;Assini, Duzzioni et al 2009;Haettig, Stefanko et al 2011;Haettig, Sun et al 2013), we cannot assume that our stable condition is also dependent on the hippocampus. Object-displacement memory requires the animal to experience only one event, in the object space task the animal experiences multiple events of the same spatial configuration.…”
Section: Discussionmentioning
confidence: 99%